2007
DOI: 10.1111/j.1365-2842.2007.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validation of a Brazilian version of the Oral Health Impact Profile for assessing edentulous subjects

Abstract: The aims of this study were to evaluate the reliability and to validate a Brazilian version of Oral Health Impact Profile for assessing edentulous subjects (OHIP-EDENT), an inventory for measuring oral health-related quality of life of edentulous subjects. The sample comprised 65 complete denture wearers (23 men, mean age of 69.1 +/- 10.3 years). The translated OHIP-EDENT was applied on two occasions with a washout period of 3 months. Reliability was assessed by an internal consistency analysis and a test-rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
0
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(160 citation statements)
references
References 16 publications
7
136
0
17
Order By: Relevance
“…In this study, satisfaction was determined using the OHIP-EDENT questionnaire (the Brazilian Portuguese version), which has been validated in the literature, to detect the impact of oral health on the quality of life of patients with total prostheses (overdentures and fixed types), (17). The vast majority (82%) of previous studies that have reported the influence of prosthetic treatment on the quality of life of patients have used non-validated instruments to assess patient satisfaction (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, satisfaction was determined using the OHIP-EDENT questionnaire (the Brazilian Portuguese version), which has been validated in the literature, to detect the impact of oral health on the quality of life of patients with total prostheses (overdentures and fixed types), (17). The vast majority (82%) of previous studies that have reported the influence of prosthetic treatment on the quality of life of patients have used non-validated instruments to assess patient satisfaction (22).…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Souza et al (17) translated the OHIP-EDENT into Portuguese, and this version was then back-translated into English. Each question was evaluated to make sure no change in meaning had been generated in the Portuguese translation.…”
Section: Measurements Questionnairementioning
confidence: 99%
“…Ao final da consulta, responderam individualmente aos questionários Oral Health Impact Profile (OHIP-EDENT) 13 , para avaliar o impacto da condição oral na qualidade de vida, e escala visual analógica (EVA) 14 , para avaliar o grau de satisfação com a reabilitação nos seguintes critérios: conforto, estabilidade/retenção, função mastigatória, estéti-ca, fonética, alteração do paladar e dor.…”
Section: Materiais E Métodounclassified
“…A comparação foi realizada entre os grupos e dentro do mesmo grupo antes e após 90 dias da intervenção (KIMOTO et al, 2006;SOUZA et al, 2007).…”
Section: Delineamento Do Estudounclassified
“…Este período de 90 dias foi escolhido para evitar que os pacientes se recordassem das respostas dadas na primeira vez, sendo denominado de "wash-out" (SOUZA et al, 2007). Um pesquisador treinado (P2), cego quanto ao grupo, foi responsável pela aplicação do questionário.…”
Section: Variável Reportada Pelo Paciente: Ohrqolunclassified